The Role of Dhikr Therapy in Maintaining Family Resilience in the Digital Era - Ramadhon, Raaf Sanjani (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
The digital era has changed family life in many ways, creating both opportunities and challenges. While technology makes communication and access to information easier, it also often causes problems such as gadget overuse, social media addiction, and weaker family interaction. These challenges may reduce family resilience if not addressed properly. Dzikir therapy, as a spiritual practice in Islam, is not only a form of worship but also has therapeutic effects. It can calm the heart, control emotions, and bring peace of mind. This study uses a literature review method to explore the role of dzikir therapy in strengthening family resilience in the digital era. In addition, this study also takes into account the context of the COVID-19 pandemic that began in March 2020 and continued until the recovery phase around 2022, which had a major impact on family resilience and adaptation strategies. The results show that dzikir therapy helps families by increasing emotional stability, building better communication, and reinforcing religious values as guidance in facing digital challenges. Furthermore, the interpretation of family resilience in this study refers to the ability of families to adapt, manage crises, and maintain harmony both in normal times and in extraordinary conditions such as the pandemic. In conclusion, dzikir therapy can be applied as part of Islamic family counseling to support family resilience. Families and counselors are encouraged to make dzikir a regular practice so that technology can be used wisely without reducing harmony and togetherness.